An experimental investigation into the behaviour of antifoaming agents. (16th March 2017) - McClure, Dale D.; Lamy, Marine; Black, Lachlan; Kavanagh, John M.; Barton, Geoffrey W.
Abstract: As part of an on-going research program into the development of accurate computational fluid dynamics models of industrial bubble column bio-reactors, the behaviour of a range of commercially available antifoaming compounds was investigated. Experimental data from a laboratory scale system showed that increasing the antifoam concentration led to a decrease in the Oxygen Transfer Rate (OTR) up to a critical value, hypothesised to be related to the monolayer coverage of the gas-liquid interface; further increases in antifoam concentration had no additional impact. Beyond this critical antifoam concentration, a 3–5 fold reduction in the OTR was found, this reduction being independent of the type of antifoam used or the superficial air velocity. The issue of antifoam 'deactivation' was also examined with the results obtained being consistent with the deactivation of polyethylene oxide type antifoams being caused by their displacement from the gas-liquid interface by more hydrophobic material. Highlights: Impact of commercially available antifoams on oxygen transfer examined. Effect of both superficial velocity and antifoam concentration quantified. OTR observed to decrease up to a critical value. This critical value is related to the monolayer concentration of the antifoam. Deactivation of polyethyleneoxide type antifoams examined.